Multi-walled carbon nanotube modified basal plane pyrolytic graphite electrodes: Exploring heterogeneity, electro-catalysis and highlighting batch to batch variation - Jones, C; Jurkschat, K; Crossley, A; Banks, C (2008)
We highlight the heterogeneity and electro-catalysis of multi-walled carbon nanotubes which is shown to be dependant on batch to batch variation via the use of cyclic voltammetry, X-ray photoelectron spectroscopy and transmission electron microscopy. Batch to batch variation is often an overlooked parameter which may limit their use in electrochemistry, and in particular, in the development and realisation of commercial electroanalytical sensors and therefore needs to be considered.